Effect of Calsporin on Nursing Piglet Growth Performance and Fecal Microflora - M. B. Menegat; C. M. Vier; H. S. Cemin; D. Shawk; J. M. DeRouchey; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 26 lactating sows (DNA 241, DNA Genetics, Columbus, NE) and litters were used in a discovery study to evaluate the effects of Calsporin, a direct-fed microbial containingBacillus subtilisC-3102, on fecal microflora of nursing pigs. The treatments consisted of providing a daily oral dose of Calsporin or a placebo control to piglets during the nursing phase. Sows were randomly assigned to treatments based on farrowing date, parity, and initial BW. The treatments were applied individually to piglets once a day from d 2 after farrowing and equalization until weaning on d 19. Sow BW, sow ADFI, piglet BW, piglet weight gain, litter size, and mortality were recorded on a weekly basis until weaning. Fecal scoring was conducted to categorize the consistency of the feces using a numerical scale from 1 to 5. Also, fecal samples were collected directly from the rectum of the piglets and pooled by litter for microbial analysis. Fecal scoring and microbial analysis were performed on d 2 after birth, and after 1 or 2 weeks of treatment. As expected, and not a primary objective of this study, there was no evidence for differences among treatments on sow and litter performance (P>0.085). There was no evidence for differences on fecal score at the beginning of the trial and after 1 or 2 weeks of Calsporin supplementation (P>0.358). Microbial analysis revealed an increase in levels of totalBacillussp. (P<0.001) and a decrease in total aerobes (P<0.026) in litters treated with Calsporin. There was no evidence for differences in number ofLactobacillussp.,Enterococcussp.,Clostridiumperfringens, Enterobacteriaceae, and total anaerobes between control- and Calsporin-treated litters (P>0.05). In conclusion, once per day supplementation of Calsporin to nursing pigs resulted in slight changes in fecal microflora, but there was no influence on nursing pig fecal consistency.
Keywords: Bacillus subtilis; diarrhea; lactation; probiotic